2021
DOI: 10.1088/1361-6641/abfadf
|View full text |Cite
|
Sign up to set email alerts
|

Impact of terbium inclusion on the photodetection performance of ZnO thin films

Abstract: Terbium (Tb)-doped ZnO thin films were fabricated using the successive ionic layer adsorption and reaction route. Their structural, morphological, optical, and ultraviolet photosensing properties were studied and compared with those of pure ZnO thin films. The x-ray diffraction results illustrate that the pure and Tb-doped ZnO films reveal hexagonal structures with the P63mc space group. The 1% Tb-doped ZnO film shows an increase in the absorption and a decrease in bandgap value from 3.24 eV to 3.15 eV compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This observation revealed that the 5 wt% Cu doped ZnO sample showed higher R value due to its uniform surface morphology with lower crystallite and grain size. Kumar et al [53], reported that Terbium doped ZnO thin film showed maximum responsivity in the order of 2.21 × 10 −1 AW −1 . Adaikalam et al [54], reported that Indium doped ZnO thin films exhibited responsivity value as 1.07 AW −1 .…”
Section: Photo-sensing Analysismentioning
confidence: 99%
“…This observation revealed that the 5 wt% Cu doped ZnO sample showed higher R value due to its uniform surface morphology with lower crystallite and grain size. Kumar et al [53], reported that Terbium doped ZnO thin film showed maximum responsivity in the order of 2.21 × 10 −1 AW −1 . Adaikalam et al [54], reported that Indium doped ZnO thin films exhibited responsivity value as 1.07 AW −1 .…”
Section: Photo-sensing Analysismentioning
confidence: 99%
“…For this reason, researchers have tried to improve the electrical and optical properties of Cu 2 O by incorporating various transition metals such as cobalt [35], iron [35,36], manganese (Mn) [22,35,[37][38][39][40] and nickel [35]. In addition, the incorporation of other elements such as aluminium [41], cerium [42], lithium [43][44][45], magnesium (Mg) [1,43,[46][47][48], silver [41], sodium [44], samarium [49], titanium [44] and zinc [42,43,50] has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%